Rekonstruksi Konstelasi Proporsi Denah Bangunan Cagar Budaya Zaman Kolonial Belanda - Nugroho, Slamet; Siahaan, Uras; Sudarwani, M. Maria (Syntax Literate, 2025)
The quality of architecture is assessed based on the rule of proportion, which is an architectural poem. The reconstruction of the constellation of proportions can be achieved by using the method of combining and matching proportions patterns with architectural drawings of cultural heritage buildings. The method of combining proportional patterns results in geometric patterns that are easier to understand and interpret than other methods such as mathematical scale calculation and statistical methods. The research subject has an attraction in the form of differences in grid patterns between the hallway face datum and the building wall datum, which creates a complex impression on the building face. The difference in datum is suspected to be caused by the use of a progression comparison between the grid pattern of the building wall and the face of the hallway. The process of reconstructing a constellation of proportions with complex datum is thought to start from drawing plans and cuts. This research is the first step for the reconstruction of the overall proportion constellation, which can be continued with further research on the building face and architectural elements. The purpose of the research is to complete the significance of cultural heritage buildings so that the interpretation discourse can be further expanded. The method used is quantitative because it uses geometric instruments and the calculation of the average accuracy of the measurement results. The first step is to provide image data and collect proportional constellation patterns synchronously and diachronically according to the time period in which the research subject was designed. Second, verifying and correcting image data according to the results of field research. Third, combine image data with proportional constellation patterns. Fourth, choose a constellation pattern of a certain proportion because of its suitability with the image data. Then make a follow-up analysis based on the constellation pattern of the selected proportions. The acquisition of the proportional constellation pattern facilitates the interpretation of the reconstruction of the design of a cultural heritage building. This proportional constellation reconstruction method can be used on other research subjects with a condition that must be met, namely the proportional constellation patterns to be tested must have synchronous and diachronic conformity at the time the research subject is designed.